Nickel and copper concentrations in near-bottom water during METEOR cruises M136 and M137 - Scholz, Florian (PANGAEA, 2024)
Trace metal and nutrient concentration gradients in near-bottom waters were determined on research vessel meteor cruises M136 and M137 in April and May 2017. Water samples were collected at 0.5, 1.0, 2.0, 3.0 and 4.0 m above the seafloor using perestaltic pumps attached to a benthic lander. Trace metal concentrations were determined by ICP-MS. The data are used to evaluate the fate of sediment-derived trace metals in the lower water column across the Peruvian oxygen minimum zone.
Keywords: bottom water; Oxygen minimum zone; trace metals